The Legal Vacuum Regarding Constitutional Complaints Under Article 24C of the 1945 Constitution of the Republic of Indonesia and the Urgency of Expanding the Powers of the Constitutional Court - Indra Purwanto (Journal of Human Interaction and Social Studies, 2026)
This study examines the constitutional implications of the absence of constitutional complaint mechanisms within the Indonesian constitutional framework and evaluates the urgency of expanding the authority of the Constitutional Court to strengthen constitutional rights protection. Employing a non empirical normative legal research design, the study analyzes statutory provisions, constitutional doctrines, and comparative constitutional literature through statutory, conceptual, and comparative approaches. Secondary legal materials include constitutional provisions, national legislation, and scholarly works on constitutional adjudication and rights protection. The findings indicate that the current constitutional structure provides fragmented remedies that are insufficient to address direct violations of constitutional rights by public authorities. Comparative insights from established constitutional democracies demonstrate that constitutional complaint mechanisms significantly enhance access to constitutional justice, judicial accountability, and the effectiveness of rights enforcement. The study concludes that introducing constitutional complaint jurisdiction would strengthen constitutional supremacy and improve the coherence of constitutional remedies in Indonesia. The research highlights that institutional reform is necessary to bridge gaps in constitutional protection and to enhance the responsiveness of constitutional adjudication to contemporary governance challenges.